New B-lymphocyte-specific enhancer-binding protein. - Dorn, A (1989)
We report the discovery of a new B-lymphocyte-specific enhancer-binding protein. A series of gel retardation assays using fragments that scan the -2172 to -1180 region of the major histocompatibility complex class II gene E alpha reveal a site (W) that serves as the recognition sequence for two nuclear proteins, one B-cell restricted and the other ubiquitously occurring. Certain characteristics of the NF-W1 and NF-W2 pair recall the OTF-2/NF-A2 and OTF-1/NF-A1 pair that binds to the immunoglobulin octamer, but we demonstrate that the two protein pairs are distinguishable by several criteria. NF-W1 and NF-W2 interact differentially with their common GTTGCATC binding site, display a different affinity for it, and have molecular weights that differ by about 20,000. Yet, proteolysis experiments and cross-linking analyses indicate that the two W complexes show structural relatedness.